Pengembangan Soal Sistem Persamaan Linear Dua Variabel Berbasis Kearifan Lokal Kabupaten Tuban untuk Melatih Student’s Higher Order Thinking Skill (HOTS) - Maulidiyawati Maulidiyawati; M. Zainudin; Ima Isnaini T.R. (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2023)
Research development that aims to produce Higher Order Thinking Skill (HOTS) questions based on local wisdom in Tuban Regency in class VIII class VIII quality Linear Equation System of Two Variables (SPLDV). This study refers to Tessmer's formative evaluation development model which consists of 4 stages, namely (1) preliminary stage, (2) self evaluation stage, (3) prototyping stage and (4) field test stage. The results of the study were 10 HOTS SPLDV items based on local wisdom in Tuban Regency according to predetermined criteria, namely 1) having a validity coefficient for each item above 0.875; 2) The reliability index of the test score is 0.84 or is included in the very high category; 3) the difficulty level of the items is spread from easy, medium, and difficult; 4) The discriminating power of each test item is in the good category; 5) The results of the practicality test by students obtained a score of 77.8%; 6) The results of testing the effectiveness of test questions by students obtained an average of 62.96% which is included in the good category and meets the criteria for effectiveness. Based on data on validity, reliability, level of difficulty, discriminating power, practicality, and effectiveness, the Higher Order Thinking Skill (HOTS) questions based on local wisdom in Tuban Regency on the material Linear Equation System of Two Variables (SPLDV) are appropriate to use.